Spatio-temporal characterization of rock slope kinematic mechanisms through multi-parameter GNSS monitoring and consensus classification in an active open-pit mine environment - Umar, Ibrahim Haruna; Lin, Hang; Firat, Muge Elif; Yang, Chaoyi (Iop Publishing Ltd, 2025)
Progressive slope instability in open-pit mines requires advanced monitoring systems integrating high-frequency geodetic data with quantitative stability classification for statistically robust early warning beyond simple threshold alarms. This study aimed to develop and validate a cumulative total earth displacement processing (CTEDP) analysis system for integrating kinematic monitoring and consensus-based stability classification framework. Sub-daily GNSS data from five monitoring points at the Pulang Copper Mine were processed over a two-month period using the CTEDP framework (displacement derivatives, rolling statistics, and anomaly detection (Z-score +/- 2.0 thresholds)). Concurrently, five classification systems (RMR, SMR, Q-slope, SSPC, RSIS) were applied, normalized to a 0-100 scale, and integrated into a weighted consensus score. Results quantified critical instability: Point 1 reached 61.3 mm displacement at a rate of 0.85 mm day-1, while Z-scores detected anomalies (Z = +3.6 to -2.0). The consensus model starkly differentiated stability, with Points 1, 2, and 5 scoring 13.3-14.3/100 (aligning with Q-slope values of 0.009 and 95% SSPC failure probability), versus Point 4 at 72.5/100. Perfect correlation (r = 1.0) among RMR, SMR, and Q-slope indicated robust convergent validity. The CTEDP system provides a high-resolution, multi-parametric foundation for quantitative risk assessment and early warning in geotechnically complex slopes.
Keywords: rock slope stability; GNSS monitoring; kinematic analysis; open-pit mine; CTEDP methodology; RSIS classification